The impact of movement control order (MCO) on teachers’ online professional development - Ahmad Safian, Asraf Hadzwan (2023)
The pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) or COVID-19, caused the education sector in Malaysia to opt for online communication as a new norm. Due to the nature of the highly contagious pandemic, restriction orders to limit people’s daily physical interactions were implemented, including in Malaysia, with the Movement Control Order (MCO). However, even during the pandemic, teachers in Malaysia are obliged to be involved with professional development (PD) activities for at least 42 hours annually. Teachers in Malaysia are commonly involved with PD activities that require mass gatherings. With average level of ICT literacy, they only usually use processing applications for work, but rarely using ICT for telecommuting for work. This research was conducted to study the readiness, motivations, and barriers for teachers in Melaka to communicate online for their PD activities during the MCO. Also, this research was conducted to get teachers’ feedback on what can be improved for them to telecommute effectively in the future. A phenomenological approach was taken to study the events faced by the teachers using three research instruments. First, a survey was conducted on 151 teachers from primary Cluster Schools of Excellence (CSE) in Melaka. The results were analysed descriptively before being enriched by another research tool; semi-structured interview sessions conducted with 13 education administrators. The third research tool, document analysis, was conducted on the outcome of the interviews to further clarify the findings. It is discovered that the samples were not ready to telecommute for their PD activities; however, they gradually adapted to technologies during the MCO. They were positively stimulated by their personal motivations, colleague supports, and rewards through annual performance marks. Next, their online PD barriers were their household responsibilities and their other workloads. They suggested that to telecommute more effectively, teachers should be assisted financially by getting incentives to purchase gadgets and internet data. In conclusion, policymakers are suggested to continuously update teachers with latest skills and information, instead of training the teachers only after new situations or policies occur. Policymakers and middle management must also be aware of the significant effects of a positive work ecosystem and prioritising workloads among their employees. Also, the samples proposed for monetary assistance for them to be adequately equipped with ICT gadgets to work. As future research suggestions, studies can be conducted to learn about teachers’ perception towards their annual performance mark, how other countries manage their teachers’ clerical works during the pandemic, and the preparation of pre-planned SOPs for future’s benefits. Also, the studies about the practice of hybrid PD approach and methods of efficient monetary assistance for teachers to be equipped with ICT gadgets can be done too.